Implementation and testing of variable-time-delays-robust telemanipulation through master state prediction - Deliparaschos, Kyriakos M. (De Montfort University, 1999)
This project is based on the implementation and testing of variable-time-delays-robust telemanipulation through master state prediction by using high level languages (C++) and Matlab software package. Time delay compensation in teleoperation can be achieved by predicting the human arm position and force (effectively the master state). The method is based on the prediction of the master state (position xm and force fm) only, which can be much more simple and accurate than predicting the slave and the remote environment, and incorporates this in a stable force-feedback scheme. The telemanipulation method was split into its fundamental elements and implemented as a number of functions. Furthermore two different methods (interpolation, curve fitting theories) for implementing the predictor model were developed and tested. Finally, the telemanipulation method was simulated (using sinusoidal inputs as the neural input) several times and the results produced, were evaluated. Due to time limitations and programming difficulties, the programming of the force feedback joystick (role of master robot) was not included.
Keywords: Variable-time-delays-robust; Time delay